Factors Causing Students To Play Truant And Teacher's Efforts To Overcome Them - Mizanul Ilmi; Yusri Yusri (Universitas Negeri Padang, 2020)
Attendance is one of the factors supporting the success of students in learning. However, the number of students who often do not go to school without any clear explanation, they are around the school and wearing school uniforms while sitting in stalls near the school while smoking. The reason given was because of being bored in class, disliked certain subjects that were considered difficult such as mathematics, and invited by classmates to play truant.This study aims to determine what factors are causing students to play truant in SMA N 1 X Koto Singkarak as seen from the factors; (1) students themselves, (2) families, (3) schools, and (4) communities in the school environment. Research subjects were 49 students. This type of research is classified as descriptive research using a research instrument that is a questionnaire and analyzed using percentage analysis techniques.The research findings reveal that the factors causing students to play truant are in the medium category with details 1.) The factors causing students to play truant in terms of students themselves are in the high category, 2.) The factors causing students to play truant in terms of family factors are in the low category, 3.) The factors causing students to play truant in terms of the school factor are in the medium category, and 4.) the factors that cause students to play truant in terms of the community in the school environment are in the medium category.